GWAS and transcriptional analysis prioritize ITPR1 and CNTN4 for a serum uric acid 3p26 QTL in Mexican Americans. (December 2016) - Chittoor, Geetha; Kent, Jack; Almeida, Marcio; Puppala, Sobha; Farook, Vidya; Cole, Shelley; Haack, Karin; Göring, Harald; MacCluer, Jean; Curran, Joanne; Carless, Melanie; Johnson, Matthew; et al.
Abstract Background The variation in serum uric acid concentrations is under significant genetic influence. Elevated SUA concentrations have been linked to increased risk for gout, kidney stones, chronic kidney disease, and cardiovascular disease whereas reduced serum uric acid concentrations have been linked to multiple sclerosis, Parkinson's disease and Alzheimer's disease. Previously, we identified a novel locus on chromosome 3p26 affecting serum uric acid concentrations in Mexican Americans from San Antonio Family Heart Study. As a follow up, we examined genome-wide single nucleotide polymorphism data in an extended cohort of 1281 Mexican Americans from multigenerational families of the San Antonio Family Heart Study and the San Antonio Family Diabetes/Gallbladder Study. We used a linear regression-based joint linkage/association test under an additive model of allelic effect, while accounting for non-independence among family members via a kinship variance component. Results Univariate genetic analysis indicated serum uric acid concentrations to be significant heritable (h 2  = 0.50 ± 0.05, p  < 4 × 10−35 ), and linkage analysis of serum uric acid concentrations confirmed our previous finding of a novel locus on 3p26 (LOD = 4.9, p  < 1 × 10−5 ) in the extended sample. Additionally, we observed strong association of serum uric acid concentrations with variants in following candidate genes in the 3p26 region; inositol 1, 4, 5-trisphosphate receptor, type 1 (ITPR1 ), contactin 4 (CNTN4 ), decapping mRNA 1A (DCP1A ); transglutaminase 4 (TGM4 ) and rho guanine nucleotide exchange factor (GEF) 26 (ARHGEF26 ) [p  < 3 × 10−7 ; minor allele frequencies ranged between 0.003 and 0.42] and evidence ofcis -regulation for ITPR1 transcripts. Conclusion Our results confirm the importance of the chromosome 3p26 locus and genetic variants in this region in the regulation of serum uric acid concentrations.